E-B-ocimene and brood cannibalism: Interplay between a honey bee larval pheromone and brood regulation in summer dearth colonies - Mark J. Carroll; Nicholas Brown; Eden Huang (PLoS ONE, 2025)
Honey bees balance colony populations against available food resources by adjusting brood rearing during nutritionally-stressed periods. Workers limit colony populations primarily through brood cannibalism of eggs and young larvae but often resume brood rearing when conditions improve. However, extended brood cannibalism reduces brood and removes brood signals that mediate brood rearing, such as E-β-ocimene, a volatile pheromone produced by eggs, young larvae, prepupae and ovipositing queens. We examined the effects of pollen supplementation on ocimene signaling in nutritionally-stressed colonies. Pollen-deprived colonies showed declines in ocimene emissions that coincided with sustained brood cannibalism of pheromone-producing brood. In contrast, pollen-supplemented colonies reared more brood and released more ocimene. Twelve day old workers that completed adult development in pollen-deprived colonies had less well developed hypopharyngeal glands and fat bodies than workers that matured in pollen-supplemented colonies. Given that ocimene emissions increased once brood rearing resumed, we considered the possibility that ocimene may help suppress brood cannibalism and support egg retention in nutritionally stressed nuc colonies. Broodless nucleus frames were treated with synthetic ocimene releases equivalent to 3,744 L2-L3 larvae. All ocimene-supplemented nucs retained large numbers of eggs and young larvae four days after initial treatment. By contrast, half of the unsupplemented nucs cannibalized all of their eggs and L1 larvae. Most of the remaining unsupplemented nuc colonies retained fewer eggs and L1 larvae than ocimene supplemented nuc colonies. E-B-ocimene may prime nutritionally stressed workers to increase brood rearing during dearth periods by projecting the presence of healthy eggs and young larvae.